(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, we will look at the causes of osteoarthritis of the knee joints and explore the role of specific exercises in its treatment. We look at how targeted exercise can benefit people with osteoarthritis, and offer a non-invasive and holistic approach to managing this condition.